(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Job satisfaction describes how content an individual is with his or her job. It is a relatively recent term since in previous centuries the jobs available to a particular person were often predetermined by the occupation of that person’s parent. There are a variety of factors that can influence a person’s level of job satisfaction. Some of these factors include the level of pay and benefits, the perceived fairness of the promotion system within a company, the quality of the working conditions, leadership and social relationships, the job itself (the variety of tasks involved, the interest and challenge the job generates, and the clarity of the job description/requirements).The happier people are within their job, the more satisfied they are said to be. Job satisfaction is not the same as motivation, although it is clearly linked. Job design aims to enhance job satisfaction and performance methods include job rotation, job enlargement and job enrichment. Other influences on satisfaction include the management style and culture, employee involvement, empowerment and autonomous workgroups. Job satisfaction is a very important attribute which is frequently measured by organizations. The most common way of measurement is the use of rating scales where employees report their reactions to their jobs. Questions relate to relate of pay, work responsibilities, variety of tasks, promotional opportunities the work itself and co- workers.